ANALYZING MAIN CHANNEL AND BACK-CHANNEL TWEETS DURING THE OCTOBER CHURCH OF LATTER DAY SAINTS GENERAL CONFERENCE - Johns, Mark D; Nelson, Shelby (AoIR Selected Papers of Internet Research, 2015)
The purpose of this study is to investigate ways in which a particular new social medium may be being utilized among members and/or former members of the LDS church as a channel for outreach, as a means of internal communication, and as a tool for the expression of dissatisfaction. Using Lundby’s (2011) aspects of cultural belonging, we observed Twitter traffic related to the LDS church fall conference, with particular attention to hashtags such as #exmormon, #gaymormon, and #mofem. We found that attempts by disaffiliated Mormons to gain mainstream attention were largely ignored, but that interaction among ex-Mormons disaffiliated for various reasons appeared to occur. We also noted considerable evidence of continued cultural belonging among the disaffiliated.